ANALISIS KUALITAS PELAYANAN PUBLIK DI KATOR KECAMATAN SAPARUA TIMUR KABUPATEN MALUKU TENGAH - Sanaki, Iksal; Soselisa, Pieter Sammy; Almahdali, Humairah (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
This study aims to analyze the implementation of public service principles at the Saparua Timur Sub-District Office in Central Maluku Regency. The main focus of this research is four public service principles: transparency, conditionality, participation, and equality of rights. The research used a descriptive qualitative approach, involving data collection through direct observation, interviews, and documentation. The findings show that the transparency principle is well implemented through clear communication of procedures and service fees to the public. However, challenges remain in improving service efficiency, particularly regarding service time. The conditional principle is applied through training programs for staff, but public understanding of procedures still needs improvement. The participation principle is reflected in efforts to involve the public in service processes, although their understanding of the procedures is limited. Finally, the equality principle is implemented by providing non-discriminatory services, although further socialization is needed to ensure the public understands their rights and obligations. Overall, while these principles have been well applied, improvements are needed in aspects such as service efficiency and public understanding. This study is expected to contribute to enhancing the quality of public services at the sub-district level.